Microtubules-interfering agents restrict aryl hydrocarbon receptor-mediated CYP1A2 induction in primary cultures of human hepatocytes via c-jun-N-terminal kinase and glucocorticoid receptor - Vrzal, Radim; Daujat-Chavanieu, Martine; Pascussi, Jean-Marc; Ulrichova, Jitka; Maurel, Patrick; Dvorak, Zdenek (European journal of pharmacology, 2008)
Disruption of microtubules has been shown to cause suppression of inducibility of major cytochromes P450 (CYP) through several nuclear receptors. Here we tested the effects of structurally different clinically used microtubules-interfering agents (MIAs), such as colchicine, vincristine, vinblastine, nocodazole and taxol on aryl hydrocarbon receptor signaling pathway in human hepatocytes. We show that tested MIAs inhibit 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-inducible expression of CYP1A2 mRNA and restrict TCDD-dependent nuclear translocation of aryl hydrocarbon receptor. On the other hand, these MIAs increased the content of aryl hydrocarbon receptor protein and mRNA by transcriptional mechanism. We show that the MIAs activate c-Jun -N-terminal kinase (JNK), partly p38 but not extracellular-regulated protein kinase (ERK). Consistently, sorbitol, a model activator of JNK, inhibited TCDD-mediated induction of CYP1A2 mRNA and down-regulated tyrosine aminotransferase mRNA - a target gene of glucocorticoid receptor. Dexamethasone had the opposite effect on aryl hydrocarbon receptor signaling and decreased aryl hydrocarbon receptor mRNA and augmented the inducibility of CYP1A2 by TCDD. We conclude that the effects of tested MIAs on aryl hydrocarbon receptor-CYP1A2 signaling pathway are dual, i.e. they inhibit transcriptional activity and nuclear translocation of aryl hydrocarbon receptor but in parallel increase aryl hydrocarbon receptor protein and mRNA level. Microtubules destabilizers have the same effects as stabilizer taxol. This implies that aryl hydrocarbon receptor functions depend on microtubules dynamics but not integrity. Perturbation of aryl hydrocarbon receptor-CYP1A2 signaling by MIAs comprises glucocorticoid receptor-JNK and probably aryl hydrocarbon receptor-JNK/glucocorticoid receptor interactions. We also demonstrate that the effects of MIAs in human hepatocytes do not proceed via arresting cell cycle as confirmed by flow cytometry (FACS) analyses.
Keywords: Cell Cycle; kultivované buňky; messenger RNA; signální transdukce; Hepatocytes; JNK Mitogen-Activated Protein Kinases; regulace genové exprese enzymů; průtoková cytometrie; Tubulin Modulators; Microtubules; Signal Transduction; Receptors, Aryl Hydrocarbon; Receptors, Glucocorticoid; buněčný cyklus; mikrotubuly; Flow Cytometry; cytochrom P-450 CYP1A2; hepatocyty; modulátory tubulinu; Cells, Cultured; RNA, Messenger; Cytochrome P-450 CYP1A2; Humans; Gene Expression Regulation, Enzymologic; JNK mitogenem aktivované proteinkinasy; receptory aromatických uhlovodíků; receptory glukokortikoidů; lidé